MODEL PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DALAM MEWUJUDAN GOOD GOVERNANCE - Agung Budi Prastyo; Rodhi Agung Saputra; Dauri Dauri; Ricco Andreas (Faculty of Law, Universitas Pattimura, 2021)
This research is a research that aims to identify and examine the application of authority related to environmental management in Way Kanan Regency and to find a model of good environmental supervision and management in the district by the Environment Agency in realizing good governance. The method used in this study is a normative-empirical research method using a statute approach and in-depth interviews. The findings of this study are that the implementation of the authority of the environmental services in the regions is not optimal so that environmental damage occurs and the model of environmental protection and management, waste and waste that uses the principles of good governance is optimal. It is hoped that future regulations related to the authority of the environmental services in the regions must have broad powers, covering aspects of planning, implementation, supervision and law enforcement. Its duties and functions must integrate the coordination and operational functions, and there is a clear arrangement of relations between institutions related to environmental management.